Sexual and reproductive health and infertility - Babar Ali (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2023)
Infertility and Adolescent Sexual and Reproductive Health (ASRH) are significant challenges worldwide, particularly in low- and middle-income countries. Teenagers living in urban slums that are quickly developing are frequently disregarded, despite the efforts of international organizations to enhance access to services and information for residents of these areas. It is common for women to blame for infertility, even when their spouse has clinical infertility; this contributes to a bias in the relevant body of research. In order to address these issues, policies on sexual and reproductive health need to be evidence-based, they need to take into account various points of view and they need to combat negative stereotypes and inequities. Comprehensive programs that prepare healthcare providers and non-clinical service providers are crucial. This review highlights the importance of addressing systemic issues, such as gender norms and economic disparities, in promoting sexual and reproductive health care to achieve desired reproductive outcomes.